2015
DOI: 10.1017/langcog.2014.51
|View full text |Cite
|
Sign up to set email alerts
|

Factors considered and ignored in plural acquisition: Frequency rules?

Abstract: Several models of regularities behind plural overgeneralization patterns of four-year-old monolingual Germans and bi-/multilingual children acquiring German were empirically examined within the framework of single- and dual-route models. The factors taken into account were frequency, cue validity, productivity, and iconicity of plural allomorphs. In this large-scale cross-sectional study, the results of 893 children tested with a modified, validated version of the speech and language screeningMSSand of 476 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…All three markers (-s, -(e)n, -e) are iconic, productive, and the latter two are also the most frequent ones in Modern High German (Zaretsky et al 2011). All three markers do not require umlauting, which allows to avoid (potentially wrong) modifications of the stems of unknown words.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…All three markers (-s, -(e)n, -e) are iconic, productive, and the latter two are also the most frequent ones in Modern High German (Zaretsky et al 2011). All three markers do not require umlauting, which allows to avoid (potentially wrong) modifications of the stems of unknown words.…”
Section: Discussionmentioning
confidence: 98%
“…We hypothesized that German adults would prefer plural markers -s, -(e)n, and -e (all three without umlaut), both with rhyming and nonrhyming nonce nouns; the first one because of its high compatibility with borrowings including many "non-rhyme" neologisms (i.e. neologisms without clear phonotactic analogies in German) and with wordfinal phonemes, the latter two because of their high frequency in Modern High German (Zaretsky et al 2011). These three plural markers are characteristic of the answers of German preschoolers in nonce words tasks (Zaretsky et al 2013a(Zaretsky et al , 2013b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plural marking system is much less complicated in Dutch, and accuracy of plural marking was unsurprisingly higher in Dutch-speaking children. Finally, Zaretsky et al (2013Zaretsky et al ( , 2016 showed different types of overgeneralization patterns in children who spoke German as an L1 (i.e., preference for -s suffixes) or as an L2 (i.e., preference for -n suffixes and zero forms). Children with German as an L1 further tended to use only the -s suffix to mark plural on non-words, when adults tended to use both -s and -n suffixes in the same task.…”
Section: Noun Plural Marking In Germanmentioning
confidence: 92%